Validity and reliability of 15 Hz global positioning system units for assessing the activity profiles of university football players - Barr, M.; Beaver, T.; Turczyn, D.; Cornish, S. (The Journal of Strength and Conditioning Research, 2019)
Global positioning system (GPS) units have recently become popular for monitoring and assessing the workloads of football players. Currently, there is a lack of studies examining the validity and reliability of these systems for that purpose, so the aim of the current study was to determine whether 15 Hz units (SPI HPU; GPSports, Canberra, Australia) could accurately be used to describe the physical demands of football. A series of cohort studies were conducted with Canadian university football players (n = 28). To assess the accuracy of the units' ability to measure high-velocity sprinting, 12 players performed multiple electronically timed 36.6 m sprints while wearing the units. To assess the interunit reliability, 5 players wore 2 units each during a training session. An analysis of the units' validity for measuring collisions was performed by comparing the correct number of tackles and blocks notated on video by an expert rater in 2 games with the number of collisions recorded by the units. The units were accurate for measuring high-sprinting velocities (coefficient of variation [CV] = 0.9%) and had good interunit reliability for recording distances at velocities between walking and sprinting CV (1.4-7.8%). The collision algorithm filter the accompanying software uses was found to have its best balance between precision and recall using a cut-off of 2.65g for linemen and 2.9g for nonlinemen. The devices used are effective at providing acceptably valid and reliable information to describe the physical demands of football. Position-specific locomotor zones are recommended when using GPS units with football players.